Speech production and speech perception in children with speech sound disorder - Berti, Larissa Cristina [UNESP]; de Assis, Mayara Ferreira [UNESP]; Cremasco, Elissa [UNESP]; Cardoso, Ana Cláudia Vieira [UNESP] (Taylor & Francis, 2021)
The goal of the present study was to investigate the relationship between speech production (SP) and speech perception in children with Speech Sound Disorder (SSD) from both typical speech production (TSP) and child’s own atypical speech production (ASP). Ten children with SSD were evaluated by a speech production task (naming test) and two speech perception tasks (phonological contrast identification) using the PERCEFAL instrument. In the identification task, the acoustic stimulus, from typical and child’s own atypical speech productions, was presented to each child, and they needed to choose the corresponding stimulus between two pictures displayed on the computer screen. The percentages of errors on speech production (SP) task, on the identification task from TSP and ASP were calculated for each child. ANOVA showed a significant difference between speech production and speech perception. Post hoc analysis demonstrated a greater mean of errors in the ASP compared to the mean of errors in the TSP and SP performances. Only SP and ASP performances presented a significant correlation (r = 0.65). Errors involving manner and manner+place were most recurring in SP. TSP seems to precede SP; that is, children with SSD perceive more speech from typical production than they are able to produce it. The significant correlation between ASP and SP suggests that the evaluation of these skills access the children’s equivalent underlying phonological representation. A more accurate production, such as typical production, may have cues that help children with SSD to identify phonological contrasts, even if their underlying representations are overly broad or not established.
Keywords: Brazilian portuguese; developmental phonological disorders; speech perception; Speech production